2019
DOI: 10.1371/journal.pone.0222281
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of asthma and allergic rhinitis in Nigeria: A nationwide survey among children, adolescents and adults

Abstract: PurposeAsthma is an important cause of morbidity and mortality worldwide and information on the prevalence of asthma in Nigeria is inconsistent. Nationally representative data, important for health planning is unavailable. We aimed to determine the current prevalence of asthma and allergic rhinitis in Nigeria.Materials and methodsA cross-sectional population survey conducted between June 2017 and March 2018 across five cities representing five geo-political zones in Nigeria. Validated screening questionnaires … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 37 publications
1
44
0
3
Order By: Relevance
“…The rate of diagnosed asthma among these students (7.2%) is much higher than in the general population in Lagos (2.3%). 27 Schooling on a university hospital campus infers good access to high-quality medical care which is likely to promote health-seeking behavior and disease diagnosis among this group compared to the general population. Furthermore, most participants with obstructive impairment had a previous physician diagnosis of asthma, suggesting substantial clinical recognition of obstructive impairment that provides opportunity for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of diagnosed asthma among these students (7.2%) is much higher than in the general population in Lagos (2.3%). 27 Schooling on a university hospital campus infers good access to high-quality medical care which is likely to promote health-seeking behavior and disease diagnosis among this group compared to the general population. Furthermore, most participants with obstructive impairment had a previous physician diagnosis of asthma, suggesting substantial clinical recognition of obstructive impairment that provides opportunity for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Community and school-based studies on childhood bronchial asthma in Nigeria estimated the prevalence rates of the disease to range from 2.2% to 22.8% [5,[14][15][16][17][18][19][20][21][22][23] as shown in Table I. The reviewed studies consistently showed that childhood bronchial asthma was reported from most of the geo-political zones of the country with higher prevalence rates in urban settings compared to rural settings.…”
Section: The Prevalence and Burden Of Childhood Asthma In Nigeriamentioning
confidence: 99%
“…Asthma manifests clinically as wheeze, recurrent cough, breathlessness, and chest tightness ( Global Initiative for Asthma (GINA), 2016 ). Recent evidence from Northern Nigeria suggests that prevalence of childhood asthma is 0.2%–1.0% in the community ( Ozoh et al, 2019 ) and 3.2%–12.5% from hospital records ( Akhiwu et al, 2017 ; Ibraheem et al, 2020 ) compared to 18.4% previously reported by the International Study of Asthma and Allergies in Childhood ( International Study of Asthma and Allergies in Childhood (ISAAC) Steering Committee, 1998 ). In spite of this improved prevalence, control of childhood asthma remains a health challenge in Nigeria and other low-income countries.…”
Section: Introductionmentioning
confidence: 97%